Calreticulin variant stratified driver mutational status and prognosis in essential thrombocythemia. Issue 5 (4th April 2016) - Elala, Yoseph C.; Lasho, Terra L.; Gangat, Naseema; Finke, Christy; Barraco, Daniela; Haider, Mahnur; Abou Hussein, Ahmed K.; Hanson, Curtis A.; Ketterling, Rhett P.; Pardanani, Animesh; Tefferi, Ayalew
Abstract : About 85% of patients with essential thrombocythemia (ET) harbor one of three driver mutations: JAK2, calreticulin ( CALR ), and MPL ; the remaining ( ∼15%) are wild type for all three mutations and are referred to as being "triple negative." Furthermore, CALR mutations in ET are structurally classified as type 1/type 1‐like or type 2/type 2‐like variants. The objective of the current study was to examine the impact of CALR mutation variant stratified driver mutational status on overall (OS), myelofibrosis‐free (MFFS), thrombosis‐free, and leukemia‐free survival (LFS) in ET; 495 patients (median age 58 years; 61% females) with ET were fully annotated for the their driver mutational status: 321 (65%) harbored JAK2, 109 (22%) CALR, and 12 (2%) MPL mutations and 11% were triple‐negative. Among the 109 CALR ‐mutated cases, 52% were classified as type 1/type 1‐like and 48% as type 2/type 2‐like. In univariate analysis, triple‐negative patients displayed the best and MPL mutated the worst OS ( P = 0.007); however, the difference in OS was no longer apparent on multivariable analysis that included age and sex as covariates ( P = 0.5). LFS was also similar among the different mutational groups ( P = 0.6) whereas MFFS was significantly shorter in MPL ‐mutated patients on both univariate and multivariable analyses (age‐adjusted P = 0.02; HR 7.9, 95% CI 2.0–31.5). Also in multivariable analysis that included thrombosis history, age, and cardiovascular risk factors, the presence of JAK2 or MPL mutations was independently associated with higher risk of thrombosis ( P = 0.02; HR 1.9, 95% CI 1.1–3.4). In conclusion, driver mutational status in ET does not appear to influence overall or LFS, even after CALR variant stratification. However, the presence of MPL mutations might be associated with a higher risk of fibrotic transformation and the presence of JAK2 / MPL mutations with higher risk of thrombosis. Am. J. Hematol. 91:503–506, 2016. © 2016 Wiley Periodicals, Inc.